Numbers of environmental injustice: The measurement of impunity in Mexico - Le Clercq, Juan Antonio; Cedillo, Celeste (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2022)
The Global Environmental Impunity Index Mexico 2020 develops a methodology for measuring environmental impunity levels. Environmental impunity is defined through a thick approach following green criminology and refers to the lack of investigation, prosecution, punishment, and damage reparation of crimes committed against the environment; non-compliance of environmental or climate policy objectives; and the inexistence of intergenerational strategies and policy programs. The results show low performance in Mexican states, as they reach half the maximum score they could achieve. This reflects fragile environmental policies and insufficient institutional capacities to protect ecosystems and guarantee the right to a healthy environment. We focus on the importance of measuring degrees of environmental impunity to operationalize environmental justice problems; we discuss the scope of the concept of environmental impunity; we explain the methodological design of its four dimensions, its forty-two indicators, and the statistical model of the Index; and we analyze its aggregate results. In conclusion, the need to develop more reliable systems of environmental indicators; the explanatory value of institutional capacities; and the complexity involved in measuring environmental crimes and damage are each highlighted.